Accelerated Algorithm of Least-Sguares Approximation of Signals by Exponentials for Wideband Frequency-Domain Reflectometry - Andreev, M.V.; Drobakhin, O.O.; Demyantchuk, K.A. (Радиофизика и радиоастрономия, 2002)
In the paper the possibility of acceleration of procedure of best least-squares approximation of signals by exponentials was considered. For this purpose the analytical expressions for components of gradient vector and Hessian matrix of the objective function were obtained. The algorithms of quasisolution searching were constructed. Method of conjugate gradient and modified Newton method were used. The obtained algorithms were compared with modification of Nelder-Mead method which used information about only values of objective function. The comparison of the novel method and Prony’s method and matrix pencil method was held. В статье рассмотрена возможность ускорения аппроксимации сигналов экспонентами методом наименьших квадратов. Для этого были получены аналитические выражения для компонент вектора градиента и матрицы Гессе оптимизируемой функции. Был сконструирован алгоритм поиска квазирешения. Использовались метод сопряженных градиентов и модифицированный метод Ньютона. Полученные алгоритмы были сравнены с модификацией метода Нелдера-Мида, который использует информацию только о значениях оптимизируемой функции. Было проведено сравнение нового метода с методом Прони и методом пучка матриц. У статті розглянуто можливість прискорення апроксимації сигналів експонентами методом найменших квадратів. Для цього було отримано аналітичні вирази для компонент вектора градієнта та матриці Гессе функції, що оптимізується. Було сконструйовано алгоритм пошуку квазірозв’язку. Використано метод спряжених градієнтів та модифікований метод Ньютона. Отримані алгоритми були порівняні з модифікацією методу Нелдера-Міда, який використовує інформацію тільки про значення функції, що оптимізується. Було проведене порівняння нового методу з методом Проні та методом пучка матриць.